Catheter directed thrombolysis for acute deep vein and arterial thrombosis in COVID-19: report of two cases from Sulaymaniyah, Kurdistan-Iraq: Catheter directed thrombolysis for COVID-19 thrombosis - Mirza, Aram Jamal; Taha, Abdulsalam Yaseen (Journal of the Faculty of Medicine Baghdad, 2021)
Abstract As one year elapsed since COVID-19 outbreak, venous and arterial thromboses are increasingly reported in different vascular territories. Once accessed by the virus, the endothelial cells, abundant in angiotensin converting enzyme-2 (ACE-2) protein, will be activated by the inflammatory process leading to coagulopathy and vascular lesions. Herein, we describe a case of extensive thrombosis of the infra-renal inferior vena cava and iliac femoral vein in a man of 62 and a case of acute superficial femoral artery thrombosis in a lady of 55. Both were COVID-19 confirmed cases with severe pneumonia, high D-Dimer levels and risk factors for severe disease or death. Despite presentation 1-2 weeks after the onset of thromboses, they were successfully managed by catheter directed thrombolysis (CDT) using tissue plasminogen activator (tPA). Owing to the increased morbidity and mortality of vascular thrombosis, there is a need to identify COVID-19 patients who need prophylaxis and prescribe them the right prophylactic drug (s). The excellent outcome of CDT in these two patients, from Sulaymaniyah/Iraq, supports the use of this treatment modality as a valid, safe and effective option for acute arterial and venous thromboses.